Health system financing fragmentation and maternal mortality transition in Mexico, 2000–2022 - Edson Serván-Mori; Carlos Pineda-Antúnez; Diego Cerecero-García; Laura Flamand; Alejandro Mohar-Betancourt; Christopher Millett; Thomas Hone; Rodrigo Moreno-Serra; Octavio Gómez-Dantés (International Journal for Equity in Health)
Abstract Objective To analyze the temporal and territorial relationship between health system financing fragmentation and maternal mortality in the last two decades in Mexico. Methods We conducted an ecological-longitudinal study of the maternal mortality ratio (MMR) in the 32 states of Mexico during the period 2000–2022. Annual MMRs were estimated at the national and state levels according to health insurance. We compared the distribution of individual attributes and place of residence between deceased women with and without social security to identify overrepresented demographic profiles. Finally, we mapped state disparities in MMR by health insurance for the last four political administrations. Findings MMR in Mexico decreased from 59.3 maternal deaths per hundred thousand live births in 2000 to 47.3 in 2018. However, from 2019 onwards, MMR increased from 48.7 in 2019 to 72.4 in 2022. Seven out of ten maternal deaths occurred in the population without social security from 2000 to 2018, then decreasing to six out of ten from 2020. Maternal deaths in the population without social security were more frequent among younger women, with less schooling, unmarried, and residing in rural areas, with higher Indigenous presence and greater social marginalization. From 2019 onwards, the MMR was higher in the population with social security. Conclusion The results of this study confirm the close relationship between maternal mortality and social inequalities, and suggest that affiliation with social security has ceased to be a differentiating factor in recent years. Understanding the evolution of maternal mortality between the population with and without social security in Mexico allows us to quantify the gap in maternal deaths attributed to inequalities in access to maternal health services, which can contribute to the design of policies that mitigate these gaps.